Alkaline Treatment of Oil Palm Frond Fibers by Using Extract of Oil Palm Empty Fruit Bunch Ash for Use in Natural Fiber Reinforced Composite (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
In Indonesia, 187 megaton biomass is produced from 8.11 million hectare oil palm plantation in 2009. The massive amount of biomass is mainly accounted for oil palm frond (OPF) and oil palm empty fruit bunch (EFB) which normally categorized as wastes. The properties of OPF fibers such as low density, low cost, less abrasion of equipment, safer production compare to synthetic fibers makes the fibers become an attractive reinforcement for composite. In this work, the utilization of oil palm empty fruit bunch ash is studied for OPF fiber-polyester resin composite to analyze the effect of condition processes. Water absorption, tensile and flexural strength were used to characterize the effects of alkaline treatment on modified OPF fibers in polyester resin. The work is focused on the effect of alkaline treatment time, temperature treatment and liquid to solid ratio that going to be analyzed using Response Surface Method-Central Composite Design (RSM-CCD). The highest tensile strength (44.87 MPa) resulted in 12 hours soaking time, 40ÂºC temperaturetreatment and 5:1 water to ash ratio. The highest flexural strength (120.50 MPa) was obtained at 1.3 hours soaking time, 4 dissolving ratio and 35oC temperature treatment. The lowest water absorption of composite (3.00%) is achieved on thelongest soaking time (14.7 hours), 4 dissolving ratio and 35oC temperature treatment.Keywords: Alkaline treatment; composite; palm oil empty fruit bunch ash palm oil frond.